Synthesis and antiviral activity of novel a-aminophosphonates containing 6-fluorobenzothiazole moiety. (2nd September 2017) - Xie, Dandan; Zhang, Awei; Liu, Dengyue; Yin, Limin; Wan, Jingbo; Zeng, Song; Hu, Deyu
GRAPHICAL ABSTRACT: ABSTRACT: A series of novel a-aminophosphonates containing 6-fluorobenzothiazole moiety derivatives were synthesized by one-pot reaction under microwave irradiation and their structures were characterized by IR, 1 H, 13 C, and 31 P NMR and element analysis data. Antiviral assays showed that some compounds possess good curative and protective activities against tobacco mosaic virus (TMV) in vivo at 500 µg/mL In particular, compounds diethyl [(6-fluorobenzo[d]thiazol-2-ylamino)(phenyl)methyl]phosphonate (4b ), diethyl [(6-methoxybenzo[d]thiazol-2-ylamino)(thiophen-2-yl)methyl]phosphonate (4j ) and diphenyl [(6-fluorobenzo[d]thiazol-2-ylamino)(4-methoxyphenyl)methyl]phosphonate (4q ) exhibited remarkable antiviral activities than Ribavirin against TMV and PVY. Compound diphenyl [(6-fluorobenzo[d]thiazol-2-ylamino)(4-methoxyphenyl)methyl]phosphonate (4q ) showed similar curative and protective activity against potato virus Y (PVY) to Dufulin.